The clinical journey of belantamab mafodotin in relapsed or refractory multiple myeloma: lessons in drug development - Pralay Mukhopadhyay; Hesham A. Abdullah; Joanna B. Opalinska; Prani Paka; Eric Richards; Katja Weisel; Suzanne Trudel; Maria-Victoria Mateos; Meletios Athanasios Dimopoulos; Sagar Lonial (Blood Cancer Journal)
Abstract Patients with relapsed/refractory multiple myeloma (RRMM) have a poor prognosis and a need remains for novel effective therapies. Belantamab mafodotin, an anti–B-cell maturation antigen antibody-drug conjugate, was granted accelerated/conditional approval for patients with RRMM who have received at least 4 prior lines of therapy, based on response rates observed in DREAMM-1/DREAMM-2. Despite the 41% response rate and durable responses observed with belantamab mafodotin in the Phase III confirmatory DREAMM-3 trial, the marketing license for belantamab mafodotin was later withdrawn from US and European markets when the trial did not meet its primary endpoint of superiority for progression-free survival compared with pomalidomide and dexamethasone. This review reflects on key lessons arising from the clinical journey of belantamab mafodotin in RRMM. It considers how incorporating longer follow-up in DREAMM-3 may have better captured the clinical benefits of belantamab mafodotin, particularly given its multimodal, immune-related mechanism of action with responses deepening over time. A non-inferiority hypothesis may have been more appropriate rather than superiority in the context of a monotherapy versus an active doublet therapy. Further, anticipation of, and planning for, non-proportional hazards arising from response heterogeneity may have mitigated loss of statistical power. With the aim of improving the efficacy of belantamab mafodotin, other Phase III trials in the RRMM development program (DREAMM-7 and DREAMM-8) proceeded to evaluate the synergistic potential of combination regimens in earlier lines of treatment. The aim was to increase the proportion of patients responding to belantamab mafodotin (and thus the likelihood of seeing a clear separation of the progression-free survival curve versus comparator regimens). Protocol amendments reflecting DREAMM-3 learnings could also be implemented prospectively on the combinations trials to optimize the follow-up duration and mitigate risk. The wider implications of the lessons learned for clinical research in RRMM and in earlier treatment settings are discussed.